One-pot synthesis of indoles and quinolinones from ortho-tosylaminophenyl-substituted para-quinone methides. Issue 55 (10th September 2020) - Wang, Junwei; Pan, Xiang; Rong, Quanjin; Zhao, Lei; Zhao, Lin; Dai, Weichen; Zhao, Kun; Hu, Lihong
Abstract : A facile one-pot synthesis has been developed through alkylation/acylation of ortho -tosylaminophenyl-substituted para -quinone methides followed by an intramolecular 1, 6-conjugate addition and oxidation sequence. Abstract : A facile one-pot synthesis has been developed through alkylation/acylation of ortho -tosylaminophenyl-substituted para -quinone methides followed by an intramolecular 1, 6-conjugate addition and oxidation sequence. This cascade reaction occurs readily in good yield (up to 95%), providing a divergent synthetic approach to structurally diverse 2, 3-disubstituted indoles and 3, 4-diaryl-substituted quinolinones.